Extranasopharyngeal Angiofibroma of the Frontal Sinus. Issue 5 (July 2019) - Kim, Jong Seung; Kwon, Sam Hyun; Kim, Jung Soo; Jung, Ji Yun; Heo, Sung Jae
Abstract : Abstract: Angiofibroma is a rare tumor that accounts for about 0.05% of all head and neck tumors; it mainly occurs in the region of the nasopharynx. To date, no study originating in the frontal sinus has been reported. The authors report a report of an 18-year-old male complaining of severe pain in the right periocular area, forehead, and temporal area for 1 week. Endoscopic sinus surgery in combination with trephination was used to remove the tumor and the tumor was diagnosed as angiofibroma from histopathologic examination. It is hard to consider a tumor as being angiofibroma when it is not located in the nasopharynx. In particular, although extranasopharyngeal angiofibroma can occur in all head and neck regions, a tumor which has developed in the frontal sinus is more difficult to diagnose as angiofibroma because no patients have been reported until now. With this study, surgeons now need to be aware of the possibility of occurrence of angiofibroma in the frontal sinus.